Chronic Heart Disease after Treatment of Oral Acute Chagas Disease - Antunes,Andrei Fornanciari (2016)
Abstract We describe the recurrence of cardiac abnormalities in a patient treated during the acute phase of Chagas disease after outpatient follow-up of 5 years.